PERAN ORANGTUA TERHADAP ANAK YANG MENGENDARAI SEPEDA MOTOR DI SEKOLAH MENENGAH PERTAMA NEGERI 40 KOTA PEKANBARU - Wan Steven Agust Fernando Marbun; Yoskar Kadarisman Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This thesis is titled The Parental Supervision of Children Riding Motorbikes in Junior High Schools 40 Pekanbaru City. This study aims (1) to determine the characteristics of parents of children who ride motorbikes. (2) to find out the supervision of parents in children riding motorbikes. The method used in this study is quantitative descriptive with techniques with data collection techniques namely questionnaire, observation and documentation, with a population of 96 people and a sample of 49 respondents with a sample collection technique that is Simple Random Sampling . The results showed that the age of parents who allowed children to ride motorbikes aged 36-40 years with the highest level of education was high school and his work as a housewife (not working). Parental supervision of children riding motorbikes is that parents always give advice and direction to children, parents are always responsible for violations committed by children, parents provide action to children who ride motorbikes during school hours and parents also separate pocket money and money oil against children. Violations that have been committed by children such as fighting the flow, riding motorbikes at high speed, violating traffic signs, not completing vehicles and not wearing helmets.Keywords: Supervision , Parents, Motorcycle Riders